Elemental Mapping for Characterizing of Thorium and Rare Earth Elements (REE) Bearing Minerals Using µXRF - I. W. Warmada; F. Pratiwi; A. Harijoko; T. B. Adimedha; A. W. Yogatama; I. G. Sukadana (PPIKSN-BATAN, 2022)
Thorium (Th) anomaly was found in Adang Volcanic Complexes, Mamuju Area, West Sulawesi. This element is associated with high-value elements, the rare earth elements (REE). The minerals containing Th and REE were found in veins mineralization with various types of minerals which are very difficult to identify by conventional method. This research aims to understand the distribution and characterization of Th and REE in individual minerals, using Micro X-Ray Fluorescence (µXRF) analysis and completed by Advanced Minerals Identification and Characterization System (AMICS) software. The samples were collected from vein mineralization in Hulu Mamuju Sector. The contents of Th and REE that were analyzed using X-Ray Fluorescence (XRF) completed by Inductively Coupled Plasma Mass Spectrometry (ICP-MS) are 11,550-74,480 ppm and 6,244.15-48,036.87 ppm, respectively. The minerals that contain Th and REE are britholite ((Ce,Ca)5(SiO4)3OH), aeschynite (Ce,Ca,Fe,Th)(Ti,Nb)2 (O,OH)6, cerite (Ce,Ca)9(Mg,Fe)(SiO4)3(HSiO4)4(OH)3, monazite (REE,Th(PO4)), thorite (Th(SiO4)), andthorutite (Th,U,Ca)Ti2(O,OH)6 associated with other minerals such as pyrite, actinolite, apatite, ilmenite, hematite, zircon and ankerite. Some minerals are uncommon minerals and are only characterized by detailed elemental mapping. The variety of minerals shows the condition of mineralization influenced by carbonatite magma and the hydrothermal process of mineralization